A drop in serum progesterone from oocyte pick-up +3 days to +5 days in fresh blastocyst transfer, using hCG-trigger and standard luteal support, is associated with lower ongoing pregnancy rates. Issue 2 (7th December 2022) - Uyanik, Esra; Mumusoglu, Sezcan; Polat, Mehtap; Yarali Ozbek, Irem; Esteves, Sandro C; Humaidan, Peter; Yarali, Hakan
Abstract: STUDY QUESTION: Do early- and mid-luteal serum progesterone (P4 ) levels impact ongoing pregnancy rates (OPRs) in fresh blastocyst transfer cycles using standard luteal phase support (LPS)? SUMMARY ANSWER: A drop in serum P4 level from oocyte pick-up (OPU) + 3 days to OPU + 5 days (negative ΔP4 ) is associated with a ∼ 2-fold decrease in OPRs. WHAT IS KNOWN ALREADY: In fresh embryo transfer cycles, significant inter-individual variation occurs in serum P4 levels during the luteal phase, possibly due to differences in endogenous P4 production after hCG trigger and/or differences in bioavailability of exogenously administered progesterone (P) via different routes. Although exogenous P may alleviate this drop in serum P4 in fresh transfer cycles, there is a paucity of data exploring the possible impact on reproductive outcomes of a reduction in serum P4 levels. STUDY DESIGN, SIZE, DURATION: Using a prospective cohort study design, following the initial enrollment of 558 consecutive patients, 340 fulfilled the inclusion and exclusion criteria and were included in the final analysis. The inclusion criteria were: (i) female age ≤40 years, (ii) BMI ≤35 kg/m 2, (iii) retrieval of ≥3 oocytes irrespective of ovarian reserve, (iv) the use of a GnRH-agonist or GnRH-antagonist protocol with recombinant hCG triggering (6500 IU), (v) standard LPS and (vi) fresh blastocyst transfer. The exclusion criteria were: (i) triggering with GnRH-agonist or GnRH-agonist plus recombinant hCG (dual trigger), (ii) circulating P4 >1.5 ng/ml on the day of trigger and (iii) cleavage stage embryo transfer. Each patient was included only once. The primary outcome was ongoing pregnancy (OP), as defined by pregnancy ≥12 weeks of gestational age. PARTICIPANTS/MATERIALS, SETTING, METHODS: A GnRH-agonist (n = 53) or GnRH-antagonist (n = 287) protocol was used for ovarian stimulation. Vaginal progesterone gel (Crinone, 90 mg, 8%, Merck) once daily was used for LPS. Serum P4 levels were measured in all patients on five occasions: on the day of ovulation trigger, the day of OPU, OPU + 3 days, OPU + 5 days and OPU + 14 days; timing of blood sampling was standardized to be 3–5 h after the morning administration of vaginal progesterone gel. The delta P4 (ΔP4 ) level was calculated by subtracting the P4 level on the OPU + 3 days from the P4 level on the OPU + 5 days, resulting in either a positive or negative ΔP4 . MAIN RESULTS AND THE ROLE OF CHANCE: The median P4 (min–max) on the day of triggering, day of OPU, OPU + 3 days, OPU + 5 days and OPU + 14 days were 0.83 ng/ml (0.18–1.42), 5.81 ng/ml (0.80–22.72), 80.00 ng/ml (22.91–161.05), 85.91 ng/ml (15.66–171.78) and 13.46 ng/ml (0.18–185.00), respectively. Serum P4 levels uniformly increased from the day of OPU to OPU + 3 days in all patients; however, from OPU + 3 days to OPU + 5 days, some patients had a decrease (negative ΔP4 ; n = 116; 34.1%), whereas others had an increase (positive ΔP4 ; n = 220; 64.7%), in circulating P4 levels. Although the median (min–max) P4 levels on the day of triggering, the day of OPU, and OPU + 3 days were comparable between the negative ΔP4 and positive ΔP4 groups, patients in the former group had significantly lower P4 levels on OPU + 5 days [69.67 ng/ml (15.66–150.02) versus 100.51 ng/ml (26.41–171.78); P  < 0.001] and OPU + 14 days [8.28 ng/ml (0.28–157.00) versus 19.01 ng/ml (0.18–185.00), respectively; P  < 0.001]. A drop in P4 level from OPU + 3 days to OPU + 5 days (negative ΔP4 ) was seen in approximately one-third of patients and was associated with a significantly lower OPR when compared with positive ΔP4 counterparts [33.6% versus 49.1%, odds ratio (OR); 0.53, 95% CI; 0.33–0.84; P  = 0.008]; this decrease in OPR was due to lower initial pregnancy rates rather than increased overall pregnancy loss rates. For negative ΔP4 patients, the magnitude of ΔP4 was a significant predictor of OP (adjusted AUC = 0.65; 95% CI; 0.59–0.71), with an optimum threshold of −8.73 ng/ml, sensitivity and specificity were 48.7% and 79.2%, respectively. BMI (OR; 1.128, 95% CI; 1.064–1.197) was the only significant predictor of having a negative ΔP4 ; the higher the BMI, the higher the risk of having a negative ΔP4 . Among positive ΔP4 patients, the magnitude of ΔP4 was a weak predictor of OP (AUC = 0.56, 95% CI; 0.48–0.64). Logistic regression analysis showed that blastocyst morphology (OR; 5.686, 95% CI; 1.433–22.565; P  = 0.013) and ΔP4 (OR; 1.013, 95% CI; 0.1001–1.024; P  = 0.031), but not the serum P4 level on OPU + 5 days, were the independent predictors of OP. LIMITATIONS, REASONS FOR CAUTION: The physiological circadian pulsatile secretion of P4 during the mid-luteal phase is a limitation; however, blood sampling was standardized to reduce the impact of timing. WIDER IMPLICATIONS OF THE FINDINGS: Two measurements (OPU + 3 days and OPU + 5 days) of serum P4 may identify those patients with a drop in P4 (approximately one-third of patients) associated with ∼ 2-fold lower OPRs. Rescuing these IVF cycles with additional P supplementation or adopting a blastocyst freeze-all policy should be tested in future randomized controlled trials. STUDY FUNDING/COMPETING INTEREST(S): None. S.C.E. declares receipt of unrestricted research grants from Merck and lecture fees from Merck and Med.E.A. P.H. has received unrestricted research grants from MSD and Merck, as well as honoraria for lectures from MSD, Merck, Gedeon–Richter, Theramex, and IBSA. H.Y. declares receipt of honorarium for lectures from Merck, IBSA and research grants from Merck and Ferring. The remaining authors declare that they have no conflict of interest. TRIAL REGISTRATION NUMBER: The study was registered at clinical trials.gov (NCT04128436).